2008
DOI: 10.1029/2008pa001637
|View full text |Cite
|
Sign up to set email alerts
|

Sahel megadroughts triggered by glacial slowdowns of Atlantic meridional overturning

Abstract: [1] The influence of the large-scale ocean circulation on Sahel rainfall is elusive because of the shortness of the observational record. We reconstructed the history of eolian and fluvial sedimentation on the continental slope off Senegal during the past 57,000 years. Our data show that abrupt onsets of arid conditions in the West African Sahel were linked to cold North Atlantic sea surface temperatures during times of reduced meridional overturning circulation associated with Heinrich Stadials. Climate model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
253
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 243 publications
(283 citation statements)
references
References 73 publications
26
253
3
1
Order By: Relevance
“…Although it is probably not a driver of abrupt climate change, the tropical climate may react very sensitively to changes in the AMOC and act as an amplifier (Chiang, 2009). The climatic shifts around the tropical North Atlantic Ocean are associated with large changes in the vegetation distribution, which is likely the result of a southward shift of the tropical rainbelt, as indicated by records from the Cariaco Basin (Hughen et al, 2004;Gonzalez et al, 2008), Northeast Brazil (Behling et al, 2000;Ledru et al, 2006;Dupont et al, 2010), and North West Africa (Mulitza et al, 2008;Hessler et al, 2010). These data emphasize the importance of the tropics and the changes in tropical vegetation during periods of abrupt climate change.…”
Section: Handiani Et Al: Tropical Climate and Vegetation Changes mentioning
confidence: 77%
See 1 more Smart Citation
“…Although it is probably not a driver of abrupt climate change, the tropical climate may react very sensitively to changes in the AMOC and act as an amplifier (Chiang, 2009). The climatic shifts around the tropical North Atlantic Ocean are associated with large changes in the vegetation distribution, which is likely the result of a southward shift of the tropical rainbelt, as indicated by records from the Cariaco Basin (Hughen et al, 2004;Gonzalez et al, 2008), Northeast Brazil (Behling et al, 2000;Ledru et al, 2006;Dupont et al, 2010), and North West Africa (Mulitza et al, 2008;Hessler et al, 2010). These data emphasize the importance of the tropics and the changes in tropical vegetation during periods of abrupt climate change.…”
Section: Handiani Et Al: Tropical Climate and Vegetation Changes mentioning
confidence: 77%
“…The position of the ITCZ over the tropical Atlantic Ocean is, in turn, linked to North Atlantic sea surface temperatures (SSTs) over the last glacial period, as suggested by several proxy studies (e.g. Peterson et al, 2000;Mulitza et al, 2008). During HE1, the northernmost position of the ITCZ likely shifted southward leading to a drier climate in West Africa and northern South America (e.g.…”
Section: Handiani Et Al: Tropical Climate and Vegetation Changes mentioning
confidence: 99%
“…Most of the GCMs in this model inter-comparison (CCSM3, KCM and MPI-UW) simulate a MWT in the Indian and African monsoon regions which is delayed with respect to the insolation forcing. This can be explained by strong feedbacks between the insolation, land evapotranspiration and cloudiness as described by Mulitza et al (2008). In the MPI-UW simulation this negative feedback related to clouds and precipitation is partly compensated by the positive vegetation-albedo feedback in these regions as savanna is partly replaced by tropical and temperate forests (not shown).…”
Section: The Monsoon and The Simulated Lig Temperature Evolutionmentioning
confidence: 99%
“…While millennial-scale hydroclimatic variations in northwest Africa are commonly linked to atmospheric processes involving latitudinal migrations of the intertropical convergence zone (ITCZ) related to North Atlantic climate anomalies (Dahl et al, 2005;Stouffer et al, 2006;Tjallingii et al, 2008;Mulitza et al, 2008;Itambi et al, 2009, Penaud et al, 2010Bouimetarhan et al, 2012;Kageyama et al, 2013), the mechanisms responsible for tropical southeastern African climate fluctuations remain a matter of debate. While it has been suggested that Indian Ocean sea surface temperatures (SST) influence eastern African rainfall variability on longer timescales (Tierney et al, 2008Tierney and deMenocal, 2013;Stager et al, 2011), other studies suggest that eastern African rainfall variations were atmospherically linked to North Atlantic climate fluctuations through a southward shift of the ITCZ (Johnson et al, 2002;Broccoli et al, 2006;Brown et al, 2007;Castañeda et al, 2007;Schefuß et al, 2011;Chiang and Friedman, 2012;.…”
Section: Introductionmentioning
confidence: 99%